Cytomorphological and physicochemical evaluations of cryptocoryne spiralis - Prasad S.K.; Sahu A.N.; Hemalatha S. (My University, 2025)
Cytomorphological and physicochemical evaluations of rhizomes of Cryptocoryne spiralis, used as a substitute of Aconitum heterophyllum for treatment of diarrhea in the Indian Siddha medicine, were carried out. The study included macroscopical and microscopical description of rhizomes of plant. Physicochemical parameters including ash values, extractive value loss on drying, foaming index, swelling index, and foreign matter were evaluated. Pesticide residue, starch grains, total saponin content, total hemolytic activity, fluorescence drug analysis, and phytochemical screening of rhizomes extracts were done. Total phenols, tannins, flavonoids, flavonols, and total alkaloids were quantified from the ethanolic extract. In vitro antioxidant activity of the extract was determined by total antioxidant capacity, reducing power assay, and scavenging methods including 2,2-diphenyl-1-picrylhydrazyl, nitric oxide, H2O2, and deoxyribose. The parameters obtained in the present study may be used as referential information for identification and authentication of plant material. © 2012 Copyright Taylor and Francis Group, LLC.